A través de las cartas - Un estudio sobre Magic : The Gathering y sus interacciones sociales entorno a este juego de mesa (2020)
Argumentative text about the importance of the card game Magic: The Gathering amongst its player base and the different ways in which the players develop social interactions centered around this game.